Corporate Social Responsibility a Mitigation Strategy for Social Risk - Nsikan Ekwere (Business Administration Department - Universitas Katolik Parahyangan, 2015)
Social Risk (SR) is a relatively new field in business management. However, social impacts are visible and can lead to operational, legal, regulatory and financial risks. Local incidents can be magnified locally and globally. Fully internalizing social risk issues is an evolutionary process for many companies. A key issue is how to ensure institutional commitment, consistency across the enterprise and in varied contexts, and durability overtime with regard to social performance. This study considers CSR as a tool companies can adopt to reduce SR and argues that if business managers are known for their impressive performances by way of delivering profits from operations within their operational environment to shareholders, they have also a responsibility to contribute to the development of the local communities they operate in; developments that would create positive impacts on the people and society and thereby reduce youth restiveness and other vices seen as SR drivers. Therefore, the paper concludes that the effective and efficient application of corporate social responsibility by companies operating in a community would go a long way in reducing the level of social risk drivers, improve infrastructural development and sustainable peace in that community. Keywords: Social Risk, Mitigation Strategy, Corporate Social Responsibility